Antioxidant activity of fractions isolated from hemolymph of garden snail Helix lucorum - Albena Alexandrova; Lubomir Petrov; Lyudmila Velkova; Aleksander Dolashki; Elina Tsvetanova; Almira Georgieva; Pavlina Dolashka (GarVal Editorial Ltda., 2021)
Context: The snail hemolymph is a multi-component mixture comprising various substances with pharmacological activity. Aims: To evaluate the antioxidant activity of hemocyanin and fractions isolated of hemolymph from garden snail Helix lucorum. Methods: The antioxidant activity was tested in chemical systems generating superoxide radicals (O2•-) and hydroxyl radicals (•OH) and was presented as percent inhibition. The fractions' composition was analyzed by MALDI-TOF/TOF mass spectrometry. Results: At concentration of 90 µg/mL the hemolymph fraction with compounds with molecular weight (MW) <100kDa demonstrated the strongest O2•-- scavenger effect (82%), followed by the hemocyanin (58%), and hemolymph fraction with compounds with MW<1kDa (15%). The most powerful •OH scavenger effect at concentration of 90 µg/mL showed hemocyanin (43%) followed by MW<100kDa fraction (26%). No •OH scavenger effect was observed by the MW<1kDa fraction. The highest chelation properties (55%) were demonstrated by the MW<100kDa fraction at concentration of 130 µg/mL; both the hemocyanin and MW<1kDa hemolymph fraction showed 33% inhibitory effect at the same concentration. The analysis of the composition of the tested fractions revealed high content of hydrophobic surfaces in MW<1kDa fraction and presence of antioxidant enzymes-catalase, superoxide dismutase and glutathione peroxidase in MW<100kDa fraction that contribute to the overall antioxidant effect of H. lucorum hemolymph. Conclusions: The complex antioxidant effect of hemolymph from H. lucorum is thought to be related to the presence of low molecular weight peptides in the MW<1 kDa fraction including glutathione and mainly to the antioxidant enzymes in the MW<100 kDa fraction.